Single-walled carbon nanotube/polystyrene core–shell hybrids: synthesis and photoluminescence properties. Issue 17 (23rd April 2018) - Orcin-Chaix, L.; Trippé-Allard, G.; Voisin, C.; Okuno, H.; Derycke, V.; Lauret, J.-S.; Campidelli, S.
Abstract : Core–shell structures made of SWNTs and polystyrene are synthesized; the hybrids can be easily manipulated in solution and exhibit photoluminescence in film. Abstract : The formation of core–shell structures has permitted to improve greatly the emission properties of inorganic quantum dots. Single-walled carbon nanotubes, thanks to their emission in the near infrared region, are promising materials for optoelectronics. However, the extreme sensitivity of nanotubes to their environment hinders their applications. Thus, the fabrication of tailor-made functional hybrid materials that preserve the optical properties of SWNTs and facilitate their manipulation is extremely important. Here, we describe the synthesis of core–shell nanotube materials made of SWNTs and polystyrene. We developed a two-step strategy that permits to form a stable and homogeneous layer of polymer around the nanotubes by adding first polystyrene via the micelle swelling method and then by locking the structure via radical polymerisation in micelles of styrene and divinylbenzene. After polymerisation and redispersion, the nanotube hybrids can be easily manipulated in solution; they still exhibited photoluminescence properties both in solution and in the solid state demonstrating that the SWNTs embedded in their polystyrene shell are isolated one from each other.